Results of gravitational lensing and primordial gravitational waves from the POLARBEAR experiment. (February 2020) - Chinone, Y; Adachi, S; Ade, PAR; Aguilar, M; Akiba, Y; Arnold, K; Baccigalupi, C; Barron, D; Beck, D; Beckman, S; Bianchini, F; Boettger, D; et al.
Abstract: POLARBEAR is a Cosmic Microwave Background radiation (CMB) polarization experiment that is located in the Atacama Desert in Chile. The scientific goals of the experiment are to characterize the B -mode signal from gravitational lensing, as well as to search for B -mode signals created by primordial gravitational waves (PGWs). Polarbear started observations in 2012 and has published a series of results. These include the first measurement of a nonzero B -mode angular auto-power spectrum at sub-degree scales where the dominant signal is gravitational lensing of the CMB. In addition, we have achieved the first measurement of crosscorrelation between the lensing potential, which was reconstructed from the CMB polarization data alone by Polarbear, and the cosmic shear field from galaxy shapes by the Subaru Hyper Suprime-Cam (HSC) survey. In 2014, we installed a continuously rotating half-wave plate (CRHWP) at the focus of the primary mirror to search for PGWs and demonstrated the control of low-frequency noise. We have found that the low-frequency B-mode power in the combined dataset with the Planck high-frequency maps is consistent with Galactic dust foreground, thus placing an upper limit on the tensor-to-scalar ratio of r < 0.90 at the 95% confidence level after marginalizing over the foregrounds.